Assessing the Welfare Impact of Indonesia’s Conditional Cash Transfer in Botungobungo Village, North Gorontalo - Meylanda Polimango; Sudirman Sudirman; Risca Marsanti Halid; Melizubaida Mahmud; Ardiansyah Ardiansyah (Jurnal Pendidikan Ekonomi dan Bisnis, 2026)
Rural households in Indonesia experience persistent socioeconomic pressures that shape welfare through income, education, and health conditions. This study assesses whether Indonesia’s conditional cash transfer, the Family Hope Program, is associated with improved welfare in Botungobungo Village, North Gorontalo, and identifies implementation factors that may enable or constrain such gains. A quantitative descriptive design was applied during January–May 2025, covering a census of 63 beneficiary households. Program performance and welfare improvement were measured using a structured questionnaire with a five-point scale, supported by observation, interviews, and document review. Instrument testing confirmed strong measurement quality (item correlations above the critical threshold; internal consistency above 0.95), and classical assumption testing indicated normally distributed residuals. Descriptive results show high beneficiary assessments of program performance (mean 4.27/5) and welfare improvement (mean 4.29/5), while still indicating gaps from the ideal. Simple linear regression demonstrates a positive association between program performance and welfare improvement (slope 0.689), with a statistically significant effect (t = 7.574 at the 5% level). The model explains 48.5% of the variance in welfare improvement, implying substantial program relevance alongside important influences beyond the transfer. Overall, the findings suggest that welfare gains are most likely when targeting accuracy, compliance with education and health conditions, and consistent monitoring support the intended human-capital pathway, and when complementary livelihood support addresses local economic constraints.